Single- versus two-port video-assisted thoracic surgery in mediastinal tumor: a propensity-matched study - Wu, Shilong (J Thorac Dis, 2019)
BACKGROUND: In this retrospective study, we aimed to compare single-port (SP) and two-port (TP) video-assisted thoracic surgery (VATS) for the surgical resection of mediastinal tumor. METHODS: Between December 2015 and October 2018, a total of 191 consecutive mediastinal tumor patients who underwent SP- or TP-VATS in the First Affiliated Hospital of Guangzhou Medical University were enrolled. Propensity-matched analysis, incorporating preoperative clinical features, was used to compare the perioperative outcomes and analyse the safety and efficacy between SP-VATS and TP-VATS for mediastinal tumor. RESULTS: There were 43 patients in the SP-VATS group, and 148 patients in the TP-VATS group from December 2015 to October 2018. Propensity matching produced 40 pairs in this retrospective study. The baseline characters were all well balanced. During the operation, the SP-VATS group showed shorter operation time (89.38 vs. 101.82 min; P=0.042) and less chest tube [16 (40.0%) vs. 28 (70.0%); P=0.007] than TP-VATS group. Postoperatively, SP and TP groups showed similar results in terms of morbidity and recovery. CONCLUSIONS: In this retrospective study, our experiences have shown that SP-VATS is a safe and promising technique and is not inferior to the TP-VATS.